Analysing of a shunt compensator installation - Soeprapto, R. Hery Satriyo; Abd Rahman, Amir Fiqri Adil; Mohd Nasir, Mohamad Na'im; Bohari, Zul Hasrizal (2014)
Nowadays, electricity has become an important part of human lives. Electricity is needed to light up houses, buildings and even transports. Electricity comes from generators which produce power that are useful for loads. But, not all power that flow from generators is useful for a power system. Although reactive power is needed on power system, a high amount of it will cause problems such as the reduction of active power generated and poor voltage regulation. The reactive power consumption by loads must be compensated and this could be done by installing shunt compensator on the electrical network. An approach has been done to study about the performance of the system with and without compensator installed. This research presents a comprehensive study on the shunt compensation method. There were three methods used in finishing this research which are collecting data from electricity utility, literature review writing, and simulation using PowerWorld Simulator. The simulated network is evaluated in terms of its performance with and without compensator installed.